Eye–Hand Coordination during Reaching. II. An Analysis of the Relationships between Visuomanual Signals in Parietal Cortex and Parieto-frontal Association Projections - Battaglia-Mayer, Alexandra; Ferraina, Stefano; Genovesio, Aldo; Marconi, Barbara; Squatrito, Salvatore; Molinari, Marco; Lacquaniti, Francesco; Caminiti, Roberto (Cerebral cortex (New York, N.Y. 1991), 2001)
The relationships between the distribution of visuomanual signals in parietal cortex and that of parieto-frontal projections are the subject of the present study. Single cell recording was performed in areas PEc and V6A, where different anatomical tracers were also injected. The monkeys performed a variety of behavioral tasks, aimed at studying the visual and motor properties of parietal cells, as well as the potential combination of retinal-, eye- and hand-related signals on cell activity. The activity of most cells was related to the direction of movement and the active position of the hand. Many of these reach-related cells were influenced by eye position information. Fewer cells displayed relationships to saccadic eye movements. The activity of most neurons related to a combination of both hand and eye signals. Many cells were also modulated during preparation for hand movement. Light–dark differences of activity were common and interpreted as related to the sight and monitoring of hand motion and/or position in the visual field. Most cells studied were very sensitive to moving visual stimuli and also responded to optic flow stimulation. Visual receptive fields were generally large and extended to the periphery of the visual field. For most neurons, the orientation of the preferred directions computed across different epochs and tasks conditions clustered within a limited sector of space, the field of global tuning. This can be regarded as an ideal frame to combine spatially congruent eye- and hand-related information for different forms of visuomanual behavior. All these properties were common to both PEc and V6A. Retinal, eye- and hand-related activity types, as well as parieto-frontal association cells, were distributed in a periodic fashion across the tangential domain of areas PEc and V6A. These functional and anatomical distributions were characterized and compared through a spectral and coherency analysis, which revealed the existence of a selective ‘match’ between activity types and parieto-frontal connections. This match depended on where each individual efferent projection was addressed. The results of the present and of the companion study can be relevant for a re-interpretation of optic ataxia as the consequence of the breakdown of the combination of retinal-, eye- and hand-related directional signals within the global tuning fields of parietal neurons.